An Analysis of Students’ Errors in Writing Personal Experience - Andriani, Desi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
There are four skills of English. They are reading, speaking, listening and writing. For some students, writing is the most difficult skill. Writing needs a complex components, such as vocabulary, grammar, spelling and word order. This research was examined students’ writing personal experience. This is a descriptive research. The research was done at UPI YPTK Padang. The population was students of UPI YPTK Padang. The sample was management students. Sample used purposive sampling. The research chose a class as sample. It was management seven class. They were forty-five students. The data were taken using test. The test is writing test. Students asked to write their own experience. The errors of students’ writing were analyzed. The result of analysis showed that students had error in writing simple past sentence, passive voice, compound sentence, noun and comparison degree.